PHENOLOGY OF AUTUMN TUNDRA DEVELOPMENT - Babaxanova M.; Nurmuxamedov D. N; Boboxonova M. A. (Web of Journals Publishing, 2025)
The article presents data on the phenology of the winter moth (Agrotis segetum) monitored in the conditions of the Pskent district, Tashkent region. It is noted that in the 2024 season, the pest developed in 4 generations and went into hibernation in the second decade of October with a fairly high sum of effective temperatures, that is, 6160 degrees. Laboratory observations recorded data on the survival of caterpillars and pupae of the winter moth, the number of oviparous females and the eggs they laid. The lifespan of the imaginal phase of the pest was established.
Keywords: Winter moth, butterflies, eggs, caterpillars, pupae, postembryonic development, vital activity indicators.